2010
DOI: 10.1161/circulationaha.109.873273
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Coronary Microvascular Dysfunction and Cardiac Energetics Impairment in Type 1 Diabetes Mellitus

Abstract: Background-Asymptomatic subjects with diabetes mellitus have an impaired cardiac energetics status that may play a significant role in the development of heart failure. In the present study, we assessed the role of microvascular dysfunction in the development of impaired cardiac energetics in subjects with type 1 diabetes mellitus. Methods and Results-Twenty-five asymptomatic subjects with type 1 diabetes mellitus (mean age Ϯ1 SD 33Ϯ8 years) and 26 age-, sex-, and body mass index-matched healthy control subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
46
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(55 citation statements)
references
References 40 publications
6
46
0
3
Order By: Relevance
“…[1][2][3] Although the underlying pathogenesis is likely to be multifactorial, [1][2][3][4] there is eventually accelerated cellular apoptosis and necrosis, resulting in increased perivascular and diffuse interstitial fibrosis within the myocardium. 2 More important, previous studies have demonstrated histological evidence of increased diffuse microscopic fibrosis in the myocardium of diabetic patients.…”
mentioning
confidence: 99%
“…[1][2][3] Although the underlying pathogenesis is likely to be multifactorial, [1][2][3][4] there is eventually accelerated cellular apoptosis and necrosis, resulting in increased perivascular and diffuse interstitial fibrosis within the myocardium. 2 More important, previous studies have demonstrated histological evidence of increased diffuse microscopic fibrosis in the myocardium of diabetic patients.…”
mentioning
confidence: 99%
“…This not only suggests that improvement in heart function was associated with correction of the metabolic abnormalities caused by elevated FFAs, but also supports the concept that diabetic cardiomyopathy may be a reversible metabolic abnormality. Increased FFAs and microvascular dysfunction are related to impaired cardiac highenergy phosphate metabolism in diabetic patients-another potential mechanism of altered PCr/ATP seen in this study (15,46).…”
mentioning
confidence: 69%
“…Accompanying their impaired cardiac energetics and function, heart failure patients also have chronically elevated plasma FFAs (43) and cognitive impairment, although a causal link between the metabolic and functional abnormalities has not been established (19). In support of the association between substrate alterations in impaired cardiac energy metabolism, patients with diabetes have low cardiac PCr/ATP ratios, unrelated to the duration of diabetes and independent of microvascular dysfunction (15,(44)(45)(46), but that correlate negatively with circulating FFA concentrations (15). There is also evidence that abnormal high-energy phosphate metabolism precedes the contractile impairment observed in heart disease (41,47).…”
mentioning
confidence: 99%
“…МР-изображения, полученные в покое и при стресс-нагрузке (инфузия аденозина), обработанные посредством программы ViewForum, были проанализи-рованы Shivu G. с соавт. [58], на их основе рассчитаны пиковые повышения свечения миокарда ЛЖ по отно-шению к крови в его полости. ИРМП рассчитывался как отношение пикового свечения при стресс-нагрузке к пиковому свечению в покое.…”
Section: магнитно-резонансная томография сердцаunclassified